GENTLEMANLY BEHAVIOUR IN JUNIOR HIGH SCHOOL AT PONDOK PESANTREN AL-URWATUL WUTSQAA BENTENG: (Perilaku Gentelmen di Sekolah Menengah Pondok Pesantren Al-Urwatul Wutsqa Benteng) - Hanafi, Muhammad; Kasman, Nuraeni; Sadapotto, Andi; Rahayu, Sri Ayu (Uniqbu Journal of Social Sciences, 2021)
This research aims to find out Causing Gentlemanly Behaviour in In Junior High School At Pondok Pesantren Al-Urwatul Wutsqaa Benteng. Type of this research is a case study. This research was carried out from April to August 2020. The Subject of this research were students of Madrasah Tsanawiyah Pondok Pesantren Al-Urwatul Wutsqaa Benteng, consist of 20 students. The sample from schools which at eight grade students. Methode of collection data was questionnaire and interview. Data analysis techniques were Sequential-parts of the study by Starovoytova and Namango with help of the program google form. The result show that: the researcher finds two factors that Causing Gentlemanly Behaviour in In Junior High School At Pondok Pesantren Al-Urwatul Wutsqaa Benteng. They are external factors and internal factors.The first category is a external factors. Out of 4 factors listed being Causing Gentlemanly Behaviour in In Junior High School At Pondok Pesantren Al-Urwatul Wutsqaa Benteng, they are The influence of ICT, Modernization of the culture, Lack of habituation manners at home, and Teacher factors. The second category is an internal factors. In this category, out of 8 factors listed being the reason that affects the students causing the loss of gentlemanly behavior in the school environment. They are the position of the social higher than the teacher, economic position is better than the teacher, students are more familiar with the material being taught, the descendants or tribe, gender, personality, talent, and love problem.